2017
DOI: 10.1002/osp4.138
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin‐6 polymorphisms with obesity or metabolic traits in young Mexican‐Americans

Abstract: SummaryObjectiveThe objective of the study is to investigate the association of interleukin‐6 (IL6) promoter single‐nucleotide polymorphisms rs1800797 (‐597 G/A) and rs1800796 (‐572 G/C) with obesity or metabolic syndrome in Mexican‐Americans.MethodsThe rs1800797 and rs1800796 single‐nucleotide polymorphisms were genotyped in Mexican‐Americans (n = 437) from South Texas, and results were correlated with measures of obesity and metabolic syndrome including body mass index, waist circumference, blood pressure, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Compared to non-vegetarian dietary patterns, vegetarian dietary patterns generate increased microbially-generated short chain fatty acids, which reduce systemic inflammation (e.g., IL-6), increase hormonal satiety-signaling (e.g., glucagon-like peptide-1) and reduce insulin resistance (32, 33). Among Hispanic/Latino subjects, recent studies suggest that IL-6 may be elevated from a young age, and the link across the lifespan to higher rates of cardiometabolic disease may be due to specific IL-6 polymorphisms in Latino youth (34). Interestingly, adding IL-6 to our models examining association with vegetarian diet exposure did not alter the protective effect of the diet on obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non-vegetarian dietary patterns, vegetarian dietary patterns generate increased microbially-generated short chain fatty acids, which reduce systemic inflammation (e.g., IL-6), increase hormonal satiety-signaling (e.g., glucagon-like peptide-1) and reduce insulin resistance (32, 33). Among Hispanic/Latino subjects, recent studies suggest that IL-6 may be elevated from a young age, and the link across the lifespan to higher rates of cardiometabolic disease may be due to specific IL-6 polymorphisms in Latino youth (34). Interestingly, adding IL-6 to our models examining association with vegetarian diet exposure did not alter the protective effect of the diet on obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that carrying the IL-6 rs1800795 G or IL-6 rs1800795 G alleles is associated with higher IL-6 protein production (19)(20)(21). Specifically, IL-6 is a cytokine which is considered a prognostic marker as well as a potential therapeutic target for BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Common polymorphisms in proinflammatory and proangiogenic cytokine genes may influence their coded protein production and play a role in the course of BC. The polymorphisms with proved functional activity are VEGFA (rs699947, rs833061, rs25648, rs1005230), IL-1β (rs1143634, rs16944), IL-1α (rs1800587) and IL-6 (rs1800795, rs1800797) (14)(15)(16)(17)(18)(19)(20)(21). Candidate gene studies as well as moderate-sized genome-wide association studies (GWAS) highlight the important role of these polymorphisms in BC risk and aggressiveness (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), although substantial heterogeneity across studies exists.…”
Section: Association Of Angiogenesis and Inflammation-related Gene Fumentioning
confidence: 99%
“…The validity and reliability of this questionnaire among Malaysian have been assessed previously [38]. Nutrients data (protein, phosphorus, potassium, magnesium and calcium) were then analysed using Nutritionist Pro™ Diet Analysis Candidate genes and SNPs were chosen from previously published literature which showed associations with metabolic traits [12,15,16,22,[40][41][42][43]. IGF1 (rs35767, rs7136446) and IL6 gene (rs1800796) polymorphisms were selected in this study.…”
Section: Estimation Of Dietary Acid Loadmentioning
confidence: 99%
“…The previous study has shown that IL6 gene -587 G/A polymorphism would increase the risk of T2DM in G allele carriers closed to 1.3 fold as compared to those with C allele [8]. The SNPs rs1800797 (-597 G/A), rs1800796 (-572 G/C) and rs1800795 (-174 G/C) that are located in the promoter region of IL6, on the other hand, were associated with obesity and metabolic traits in different ethnic groups [12]. The rs1800796 polymorphism was associated with high insulinogenic index in Danes [14], hyperglycaemia in Mexicans [15] and hypertension and obesity in Asians [16,17].…”
mentioning
confidence: 94%